The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41550-019-0865-1
|View full text |Cite
|
Sign up to set email alerts
|

Size diversity of old Large Magellanic Cloud clusters as determined by internal dynamical evolution

Abstract: The distribution of size as a function of age observed for star clusters in the Large Magellanic Cloud (LMC) is very puzzling: young clusters are all compact, while the oldest systems show both small and large sizes. It is commonly interpreted as due to a population of binary black holes driving a progressive expansion of cluster cores. Here we propose, instead, that it is the natural consequence of the fact that only relatively low-mass clusters have formed in the last ~3 Gyr in the LMC and only the most comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…These results confirm that the internal dynamical evolution tends to produce clusters with more and more compact cores, and demonstrate that the spread in core size observed for the old LMC GCs is the natural consequence of these processes. On the other hand, the analysis discussed in Ferraro et al (2019) also demonstrates that only low-mass systems have been recently (in the last ∼ 3 Gyr) formed in the LMC, and essentially all of them were generated in the innermost regions of the galaxy. Hence, they surely cannot resemble the progenitors of the currently old clusters, which are much more massive (by up to factors of 100) and orbit at any distance from the centre of the LMC.…”
Section: Reading the Signature Of The Dynamical Evolution From The Bsmentioning
confidence: 96%
See 2 more Smart Citations
“…These results confirm that the internal dynamical evolution tends to produce clusters with more and more compact cores, and demonstrate that the spread in core size observed for the old LMC GCs is the natural consequence of these processes. On the other hand, the analysis discussed in Ferraro et al (2019) also demonstrates that only low-mass systems have been recently (in the last ∼ 3 Gyr) formed in the LMC, and essentially all of them were generated in the innermost regions of the galaxy. Hence, they surely cannot resemble the progenitors of the currently old clusters, which are much more massive (by up to factors of 100) and orbit at any distance from the centre of the LMC.…”
Section: Reading the Signature Of The Dynamical Evolution From The Bsmentioning
confidence: 96%
“…Hence, deeper investigations appeared to be necessary to solve Fig. 9 The application of the "dynamical clock" to extra-Galactic clusters: N relax − A + relation for the five LMC clusters discussed in Ferraro et al (2019) (large red squares). For the sake of comparison, the sample of 48 Galactic GCs previously investigated (Ferraro et al, 2018) is shown with grey circles.…”
Section: Reading the Signature Of The Dynamical Evolution From The Bsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tight relation between these two parameters (solid line) demonstrates that the segregation level of BSSs can be efficiently used to evaluate the level of dynamical evolution experienced by the parent cluster. Right Panel: The same as in the left panel (with the sample of Galactic GCs shown in grey) with the five LMC clusters discussed in Ferraro et al (2019) highlighted as red squares.The LMC clusters ranked at increasing value of the dynamical age are NGC1841, Hodge 11, NGC2257, NGC1466 and NGC2210.…”
Section: Defining the "Dynamical Clock"mentioning
confidence: 99%
“…The "dynamical clock" has been recently used by Li et al (2019) to measure the dynamical age of 7 intermediate-age (between 700 Myr and 7 Gyr) clusters in the Large Magellanic Cloud (LMC) finding a low-level of dynamical evolution. Interesting enough, instead Ferraro et al (2019) measured the BSS segregation level in five old LMC GCs (with ages comparable to Galactic GCs) detecting clear-cut differences in their level of dynamical evolution (see the right panel of Figure 2). The figure also shows the impressive matching with the trend defined by the Galactic GCs (grey circles), demonstrating that the "dynamical clock" can be efficiently used in any stellar environment.…”
Section: Defining the "Dynamical Clock"mentioning
confidence: 99%